APLIKASI CENDAWAN ENTOMOMOPATOGEN Cordyceps militaris PADA HAMA ULAT API (Setothosea asigna) DI PERKEBUNAN SATYA KISMA USAHA UNIT BATANG GADING MUARA BUNGO JAMBI - Budi Purnama; Achmad Himawan; Samsuri Tarmadja (AGROISTA : Jurnal Agroteknologi, 2021)
The aims of this research are to determine the best medium to propagation entomopathogenic fungi C. militaris, to determine effectivity and dosage of C. militaris to control pupae of S. asigna. This research was conducted in plantation of PT. Satya Kisma Usaha Unit Batang Gading, Tanah Tumbuh County, Muara Bungo District, Jambi. The research was conducted from August to September 2020. This study used a non-factorial method, which was arranged in a completely randomizing design (CRD) with 1 factor, namely growth media. The growth media are consisted of corn seeds (M1) and bran (M2) and repeated 5 times. For dosage of fungi used a non-factorial method, which was arranged in a CRD with 1 factor, namely bran media. The bran media dosages are P0 = control (100 ml aquadest/polybag), P1 = 10 g C. militaris + 100 ml aquadest/polybag, P2 = 20 g C. militaris + 100 ml aquadest/polybag, P3 = 30 g C. militaris + 100 ml aquadest/polybag P4 = 40 g C. militaris + 100 ml aquadest/polybag and all of them are repeated 4 times. The results showed that bran medium is the best medium for fungi propagation. C. militaris was effectively to control pupae of S. asigna. The best of fungi dosage is P4 = 40 g C. militaris + 100 ml aquadest/polybag. The highest pupae mortality (100%) is achieved at 12 days observation. Keywords: entomopathogenic fungi, Cordyceps militaris, bran, Setothosea asigna